Description of Marolia alicantina sp. nov. (Coleoptera: Melandryidae) from Spain and new distribution records of Marolia species - Konvička, Ondřej; Brustel, Hervé (Zootaxa, 2021)
Marolia alicantina sp. nov. (Coleoptera: Melandryidae) from eastern Spain is described and illustrated. All specimens were collected using window traps on Quercus rotundifolia Lamarck, 1785 (Fagaceae) in the Carrascar de la Font Roja Natural Park (Alicante, Spain). M. alicantina sp. nov. is the only European Marolia having erect setae on the elytra and pronotum. M. alicantina resembles M. grandis Peyerimhoff, 1971 from north Africa, from which it can distinguished by the denser punctuation of the pronotum, shape of the base of the pronotum and shape of the aedeagus. Furthermore, unpublished records for other Marolia species are presented in this paper; in particular M. purkynei Mařan, 1933 is recorded for the first time in Croatia and Greece. The authors had the chance to study six specimens, subsequently labelled as syntypes, of the M. purkynei type series. The location of the remaining possible syntype remains unknown.